2016
DOI: 10.7759/cureus.701
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Smoking Among Final Year Medical Students: A Multicentric Survey From Pakistan

Abstract: IntroductionSmoking is the leading cause of lung cancer around the world. In a developing country like Pakistan with low levels of literacy and general awareness about adverse effects of smoking, doctors play a pivotal role in educating the masses about its harmful consequences and providing support for smoking cessation. However, their efficacy is affected if they smoke themselves, and oftentimes the habits cultivated during educational recourse are carried into the professional careers. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
3
11
0
2
Order By: Relevance
“…Another positive attitude toward hookah smoking among the students was that it could reduce anxiety and fatigue. Similar studies have also shown that the pleasure of smoking cigarette and its effect on reducing anxiety were the most important factors that increased students' tendency towards smoking (19). In the same line, various studies have shown that psychological problems, such as anxiety and depression, were the most important factors in increasing the youth's tendency to use drugs (23).…”
Section: Discussionmentioning
confidence: 51%
“…Another positive attitude toward hookah smoking among the students was that it could reduce anxiety and fatigue. Similar studies have also shown that the pleasure of smoking cigarette and its effect on reducing anxiety were the most important factors that increased students' tendency towards smoking (19). In the same line, various studies have shown that psychological problems, such as anxiety and depression, were the most important factors in increasing the youth's tendency to use drugs (23).…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, this study also suggested that men were twice as likely as compared to women in reporting that either they might start smoking cigarettes and using recreational drugs or their usage might increase. These gender disparities in use of tobacco and narcotics are frequently seen in Pakistan (31)(32)(33). Furthermore, men are more likely to suffer from non-communicable diseases (34).…”
Section: Discussionmentioning
confidence: 99%
“…One of the study suggested that proper awareness campaign of doctors and medical students to enhance their knowledge about smoking eradication from the society is very crucial. 25…”
Section: Discussionmentioning
confidence: 99%